Body, Transfeminism and Cisexism: Analysis of Two Stories by Camila Sosa Villada - Hernández Campos, Ronald Gerardo (2025)
This paper analyzes the short stories “Soy una tonta por quererte” and “Seis tetas” by Camila Sosa Villada. It focuses on the representation of the trans female body and cis-sexist violence. The author, a prominent Argentine trans writer, uses fiction to explore trans identity and embodiment, distancing herself from the autofiction that characterizes her earlier works. The analysis is based on Michel Foucault’s (2007) theory of the dispositif of sexuality, transfeminism, and the decoloniality of gender (Romero et al., 2024), as well as the concepts of cis-sexism by Facu Saxe (2021) and body grammar by Meri Torras (2015). The methodology used was discursive analysis, focusing on the interactions between trans and cisgender characters. In “Soy una tonta por quererte”, the story reveals the tension between a desired identity and a system that imposes a cis-sexist reality, reflected in the narrator’s relationship with Billie Holiday. “Seis tetas” depicts a dystopia where trans women, after being persecuted, build a resilient community. Sosa Villada critiques heteronormativity and calls for the recognition and acceptance of dissident identities. Her stories challenge cis-sexist structures and enrich literature with trans voices that promote inclusion and visibility.